Proceedings of the 29th ACM Conference on User Modeling, Adaptation and Personalization 2021
DOI: 10.1145/3450613.3456821
|View full text |Cite
|
Sign up to set email alerts
|

User-centered Evaluation of Popularity Bias in Recommender Systems

Abstract: Recommendation and ranking systems are known to suffer from popularity bias; the tendency of the algorithm to favor a few popular items while under-representing the majority of other items. Prior research has examined various approaches for mitigating popularity bias and enhancing the recommendation of long-tail, less popular, items. The effectiveness of these approaches is often assessed using different metrics to evaluate the extent to which over-concentration on popular items is reduced. However, not much a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Popularity bias has been largely investigated from the item-centered perspective, that is, how frequently popular items appear in recommendation lists. The item-centered perspective study ignores users' interest in popular or less popular items, which causes a limitation as the popularity bias does not affect users equally [3]. Recently, Abdollahpouri et al [2] have conducted a research study to look at the popularity bias from a different perspective: the users'.…”
Section: Introductionmentioning
confidence: 99%
“…Popularity bias has been largely investigated from the item-centered perspective, that is, how frequently popular items appear in recommendation lists. The item-centered perspective study ignores users' interest in popular or less popular items, which causes a limitation as the popularity bias does not affect users equally [3]. Recently, Abdollahpouri et al [2] have conducted a research study to look at the popularity bias from a different perspective: the users'.…”
Section: Introductionmentioning
confidence: 99%
“…Then, they proposed a fair re-ranking model by introducing constraints based on the 0-1 integer programming to reduce this gap. Abdollahpouri et al [3] further researched user-centered evaluation of popularity bias. They proposed a user-centered evaluation method that can effectively tackle popularity bias for different user groups while accounting for users' tolerance towards popularity bias using Jensen divergence.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, they analyzed whether such algorithmic popularity bias affects users of different genders. Contrary to the works mentioned above that focus on consumers [22,3,2], or provider fairness [1,20,38], our work studies the fairness of recommended items from both perspectives (i.e., CP-Fairness). Mehrotra et al [26] showed that blindly optimizing for consumer relevance might hurt supplier fairness.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Though long-tail SBR models like TailNet and NISER can provide more tail items, they do not consider how many tail items should be included in a recommendation list. As proposed in [30], these methods mainly take the item-centered perspective but ignore users' different preferences on tail items. To this end, we mitigate the popularity bias in SBR from the user perspective.…”
Section: Introductionmentioning
confidence: 99%